Melanopsin and Cone Photoreceptor Inputs to the Afferent Pupil Light Response - Zele, Andrew J. (Front Neurol, 2019)
Background: Retinal photoreceptors provide the main stage in the mammalian eye for regulating the retinal illumination through changes in pupil diameter, with a small population of melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs) forming the primary afferent pathway for this response. The purpose of this study is to determine how melanopsin interacts with the three cone photoreceptor classes in the human eye to modulate the light-adapted pupil response. Methods: We investigated the independent and combined contributions of the inner and outer retinal photoreceptor inputs to the afferent pupil pathway in participants with trichromatic color vision using a method to independently control the excitations of ipRGCs, cones and rods in the retina. Results: We show that melanopsin-directed stimuli cause a transient pupil constriction generated by cones in the shadow of retinal blood vessels; desensitizing these penumbral cone signals uncovers a signature melanopsin pupil response that includes a longer latency (292 ms) and slower time (4.1x) and velocity (7.7x) to constriction than for cone-directed stimuli, and which remains sustained post-stimulus offset. Compared to melanopsin-mediated pupil responses, the cone photoreceptor-initiated pupil responses are more transient with faster constriction latencies, higher velocities and a secondary constriction at light offset. The combined pupil responses reveal that melanopsin signals are additive with the cone signals. Conclusions: The visual system uses the L–, M–, and S–cone photoreceptor inputs to the afferent pupil pathway to accomplish the tonic modulations of pupil size to changes in image contrast. The inner retinal melanopsin-expressing ipRGCs mediate the longer-term, sustained pupil constriction to set the light-adapted pupil diameter during extended light exposures.